Contribuição de diferentes conteúdos das aulas de educação física no ensino fundamental I para o desenvolvimento das habilidades motoras fundamentais - de Araujo, Mauricio Pires; Barela, Jose Angelo [UNESP]; Celestino, Melissa Leandro; Forti Barela, Ana Maria (Soc Brasileira Med Esporte, 2012)
Introduction and objective: This study investigated the contribution of physical education (PE) classes in elementary school I for the development of basic motor skills of children from two public schools in the same neighborhood of São Paulo city, and if the practice of extreme sports besides the PE classes could differently contribute to the development of those skills. Methods: Nineteen children (9.5 +/- 0.3 years) who had two weekly PE classes composed the control group (CG) and 22 children (9.6 +/- 0.5 years) who had two weekly PE classes and three extreme sports classes composed the experimental group (EG). All children were videotaped while performing locomotor and object control motor skill subtests from the Test of Gross Motor Development (TGMD-2). The videos were analyzed and raw scores were obtained according to the quality of the observed movement, and equivalent motor age was also estimated for both subtests. Results: The results indicated that the EG presented higher raw scores compared to CG in the locomotor subtest and both groups presented similar scores in the object control subtest. Moreover, EG presented higher equivalent motor age in the locomotor subtest compared to CG and neither group presented differences between equivalent motor age and chronological age in the object control subtest. Conclusion: Based on these results we conclude that PE classes in elementary school appropriately contributed to the development of basic motor skills, since neither group presented difference between equivalent motor age and chronological age, and that extreme sports classes contributed even more for the development of locomotor skills.
Contribution of different contents of physical education classes in elementary school I for the development of basic motor skills
Keywords: motor development; extreme sports; motor evaluation; TGMD-2